Heterotopic Respiratory Mucosa in the Rectum: An Unusual Type and Site of Heterotopia in the Gastrointestinal Tract. (April 2019) - Bsirini, Caroline; Tirumanisetty, Pratyusha; Dytoc, Joseph N.; Agostini-Vulaj, Diana; Steevens, Christopher; Ullah, Asad; Huber, Aaron R.
Although pancreatic and gastric heterotopias are common findings in the gastrointestinal tract, heterotopic respiratory mucosa (HRM) in the rectum is extremely rare and has only been reported twice previously. We are presenting, to our knowledge, the third case of HRM in the rectum. A 56-year-old man with a history of chronic diarrhea presented for diagnostic colonoscopy, where he was found to have a rectal subepithelial nodule. He was subsequently referred to a tertiary medical center for further evaluation with rectal endoscopic ultrasound. Endoscopically, the nodule was hypoechoic, 2 to 3 mm in size, located in the submucosa, and did not appear to invade the muscularis propria. An uncomplicated endoscopic submucosal resection was subsequently performed. Microscopically, the nodule showed a multicystic complex lesion located in the submucosa, lined by ciliated pseudostratified columnar epithelium and surrounded by thin to moderately thick smooth muscle bundles and multiple lobules of seromucinous glands. There was associated acute and chronic inflammation. The rectum overlying the subepithelial lesion was lined by congested and edematous colonic mucosa and demonstrated no connection with the underlying cystic lesion. Immunohistochemical stains showed positive p63 basal cell staining in the respiratory epithelium of the lesion, while CDX2, TTF-1, and estrogen receptors were all negative. HRM is a benign nonneoplastic lesion with unclear etiology. Pathologists and gastroenterologists should be aware of this entity and consider it in their differential diagnosis for a subepithelial nodule in the rectum, keeping in mind that neoplastic processes can also develop in this location.